The relationship between sarcomerogenesis and the development of tissue organization of the myocardium in embryonic chicken cardiogenesis - Maslak, H.S.; Onysko, R.M.; Chelpanova, I.V. (Морфологія / Morphologia / Morfologìâ, 2024)
Background. The general basis for understanding how the limited range of sarcomere contraction ensures cardiac output during systole is the analysis of the ontogenetic formation and local features of the development of the myofibrillar structure of cardiomyocytes by comparing the phase states of the myocardium. The purpose of the research is to determine phase and topological features and quantitative ultrastructural characteristics of sarcomerogenesis in cardiomyocytes of chicken embryos. Methods. Embryos of Cobb500 crossbred chickens were studied from the beginning of the 6th day to the 21st day of incubation. Ultrastructural features of contractile cardiomyocytes in different areas of ventricular and atrial myocardium in systole and diastole were studied using transmission electron microscopy. Results. At the 29th stage of development of chicken embryos in diastole, immature sarcomeres had different lengths. The average length of sarcomeres was 1.86±0.09 μm in the left ventricle and 1.91±0.21 μm in the right ventricle. At the 36th stage in the state of diastole, a significant increase in the length of sarcomeres was observed in the compact myocardium of the left ventricle and left atrium, while in the right parts of the heart, the increase in Z-Z distance was less active. In the right units of the heart, sarcomeres with unequal lengths were more often found in the compact myocardium and in the trabeculae. In different areas of the myolamella and trabeculae, the degree of relaxation of sarcomeres during simulation of maximum diastole was not the same. Incomplete relaxation of sarcomeres was noted in the initial and final sections of the muscle plates. In the middle part of the trabeculae, the length of the sarcomeres was significantly longer (1.82±0.04 μm), and in the intermediate (main) part of the muscle plates of the compact ventricular myocardium, the sarcomeres were 10.4% (p<0.05) longer, than in their basis. Conclusion. By the end of prenatal cardiogenesis, the tangential orientation of the Z-discs of myofibrils and the shape of cardiomyocytes in systole was formed and strengthened due to the mutual displacement of neighboring myolamella during the counter-directional rotation of the basal and apical parts of the left ventricle during the shortening of sarcomeres to 1.83±0.04 μm. In the right ventricle and atrial myocardium, systolic contraction did not change the orthogonal orientation of telophragms and intercalated discs when sarcomeres were shortened to 1.79-1.84 μm. In the state of diastole, the orthogonal orientation of Z-discs is characteristic of contractile cardiomyocytes of all chambers when the length of sarcomeres reaches 2.17±0.07 μm in the intermediate part of the myolamella of both ventricles, 2.12±0.13 μm in the middle part of atrial and ventricular trabeculae, 2.02±0.10 μm at the base of trabeculae of all chambers and muscle plates of both ventricles.